(untitled) (Archive of Conferences, 2020)
Mahmud Amahshari is one of our great scholars whose name has been restored due to independence, whose legacy has been researched and published. He has written works in the fields of literature, lexicography, linguistics, Islamic sciences, aruz, and logic, and his legacy has captivated Eastern and Western scholars over the centuries. His place in the development of science was appreciated and he was honored with such titles as "Teacher of the World", "Jarullah", "Honor of Khorezm", "Teacher of Arabs and Ajam", "Kaaba of Writers".